The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/sdi.13039
|View full text |Cite
|
Sign up to set email alerts
|

Why and how high volume hemodiafiltration may reduce cardiovascular mortality in stage 5 chronic kidney disease dialysis patients? A comprehensive literature review on mechanisms involved

Abstract: Online hemodiafiltration (HDF) is an established renal replacement modality for patients with end stage chronic kidney disease that is now gaining rapid clinical acceptance worldwide. Currently, there is a growing body of evidence indicating that treatment with HDF is associated with better outcomes and reduced cardiovascular mortality for dialysis patients. In this comprehensive review, we provide an update on the potential mechanisms which may improve survival in HDF treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 149 publications
(179 reference statements)
0
23
0
Order By: Relevance
“…However, by achieving better patient outcomes at the same or lower costs, OL‐HDF meets the core prerequisites of patients, providers, and payers alike. There are certainly areas requiring further refinement through the acquisition of more evidence, but the current data and clinical experience with HDF are sufficiently strong to suggest its superiority over conventional HD (including high‐flux HD) based upon clinical endpoints derived from RCTs and real‐world evidence 26 . Several millions of OL‐HDF treatment sessions are carried out safely annually without increased procedure‐specific incidences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, by achieving better patient outcomes at the same or lower costs, OL‐HDF meets the core prerequisites of patients, providers, and payers alike. There are certainly areas requiring further refinement through the acquisition of more evidence, but the current data and clinical experience with HDF are sufficiently strong to suggest its superiority over conventional HD (including high‐flux HD) based upon clinical endpoints derived from RCTs and real‐world evidence 26 . Several millions of OL‐HDF treatment sessions are carried out safely annually without increased procedure‐specific incidences.…”
Section: Discussionmentioning
confidence: 99%
“…A body of clinical evidence indicates that HDF, particularly at high substitution volumes (> 21 L per treatment) provides survival benefits for patients; this has given rise to the concept of convective dose which considers the total ultrafiltration volume (volume due to substitution and weight loss 21–25 . To our knowledge to date, no studies have shown any inferiority or detrimental effects attributed to OL‐HDF 26 . Further, previous studies that were unable to demonstrate any superiority of OL‐HDF (over HF‐HD) probably applied substitution volumes below 21 L per treatment, as the convective dose concept only became evident subsequently after the initial set of clinical studies on OL‐HDF 26 …”
Section: Striving For “More Intensive” Dialysis: Hemodiafiltrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a PSM study of 1012 incident patients in Spanish Fresenius units utilizing HDF with CV > 21 L/session, all-cause and cardiovascular mortality were significantly less in the HDF-treated subjects. 33 The apparent advantage of higher CVs was explored further using PSM of two HDF populations with different CV (<4.6 and >64.8 L/wk). 16 Cardiovascular disease within the Charlson index was not specifically reported.…”
Section: Cardiovascular Outcomesmentioning
confidence: 99%
“…Today, the maximal convection dose remains unknown 43,63,64 . Mechanisms supporting clinical benefits of online HDF have been summarized in a recent review 65 Future perspectives may be envisaged with online modalities.…”
Section: Evidence‐based Facts Supporting Clinical Benefits Of Online Hdfmentioning
confidence: 99%